Mathematics

Question

Simplify each expression, and then arrange them in increasing order based on the coefficient of n2. -5(n3 – n2 – 1) + n(n2 – n) (n2 – 1)(n + 2) – n2(n – 3) n2(n – 4) + 5n3 – 6 2n(n2 – 2n – 1) + 3n2
Simplify each expression, and then arrange them in increasing order based on the coefficient of n2.  -5(n3 – n2 – 1) + n(n2 – n) (n2 – 1)(n + 2) – n2(n – 3) n2(

1 Answer

  • Answer:

    Step-by-step explanation:

    -5(n^3 - n^2 - 1) + n(n^2 - n)

    -5n^3 + 5n^2 + 5 + n^3 - n^2

    -4n^3 + 4n^2 + 5 <===

    (n^2 - 1)(n + 2) - n^2(n - 3)

    n^2(n + 2) - 1(n + 2) - n^3 + 3n^2

    n^3 + 2n^2 - n - 2 - n^3 + 3n^2

    5n^2 - n - 2 <===

    n^2(n - 4) + 5n3 - 6

    n^3 - 4n^2 + 5n^3 - 6

    6n^3 - 4n^2 - 6 <===

    2n(n^2 - 2n - 1) + 3n^2

    2n^3 - 4n^2 - 2n + 3n^2

    2n^3 -n^2 - 2n <===

    putting them in order based on the coefficient n^2 is :

    6n^3 - 4n^2 - 6

    2n^3 - n^2 - 2n

    -4n^3 + 4n^2 + 5

    5n^2 - n - 2

NEWS TODAY